Chlorogenic Acid Relieves the Lupus Erythematosus-like Skin Lesions and Arthritis in MRL/lpr Mice - Ruxuan Wang; Xiaoyi Yang; Shen You; Mengyao Hao; Jianguang Li; Xiaoguang Chen; Jing Jin (MDPI AG, 2022)
Chlorogenic acid (CGA) is a phenylpropyl substance synthesized through the shikimic acid pathway. In addition to its anti-tumor, anti-inflammatory, and antioxidant abilities, CGA also has immunomodulatory effects. The aim of the present study is to investigate the therapeutic effects of CGA on the skin damage and arthritis caused by systemic lupus erythematosus (SLE) in an MRL/lpr mouse model. In the SLE model, female MRL/lpr mice at the age of 10 weeks old were treated with CGA daily or cyclophosphamide (CTX) weekly via intraperitoneal injection for three months. After treatment, CGA can significantly alleviate the skin and mucous membrane damage caused by SLE and has a certain improvement effect on arthritis. CGA could inhibit dsDNA expression to a certain extent but has no obvious regulation on ANA concentration. The ELISA and BioMAP results indicated that CGA might play an anti-inflammatory role by down-regulating the interleukin (IL)-17 level. In conclusion, our study demonstrates that CGA can alleviate multiorgan damage in MRL/lpr mice by reducing IL-17.